Gilmer Whitley: capstone - Whitley, Gilmer, artist (Colorado State University. Libraries, 2025)
The artist's statement: The will of the Complex is integrated down to the essence of all things: every person, every landscape, every moment; the Complex is the unifier. There was a time beyond recollection when flora and fauna were naught and instead there were only specks in a primordial pool. Perhaps they sought to emulate the night sky from whence they came, or maybe they just enjoyed swimming in the water, but in the time since they remade the world into a Gaia with new pools fit for the coyotes and the roots to drink and when the water became the clouds it could fly eternal and take any form possible and still the night sky was the same. However, the Complex is as hungry as it is giving and everyone ought to learn quickly not to touch fire, beautiful though it is. Integration always has its terms; few things grow in the alpine and we dare not dwell long, for the Romantics knew that Gaia's horrors were also her glories, and nothing has changed since; in love as in terror, but everywhere there is beauty: rocks can flow like rivers and dunes can tower above mountains and a single person can have soulmates uncountable. As unlikely as reality is, it is, and there is no such thing as nothing. Reality can seem to warp or destabilize, but somewhere there is ground to set upon and a sea in which to swim and so one ought to recognize the Complex from their node of existence as it expands infinitely before them.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting